Macskazene Ybl Miklós lakásánál - Gelencsér, József (Közép-Európai Közlemények, 2016)
Miklós Ybl (1814-1891) was one of the most important Hungarian architects of the 19th century. In 1865 he was mandated to design, build and furbish the temporary house of representatives. The deadline was short for the completion and handing over of the new public building, which was placed in Pest (today called Budapest), close to the National Museum. With respect to the short deadline and the higher professional skills, Ybl mandated furniture carpenters from Vienna to prepare the fixtures and furniture. This move offended the craftsmen in Pest both financially and with respect to their professional pride. These craftsmen together with other Hungarians offended in their national pride by the move organised a shivaree (charivari) event in front of the house of Ybl and the protestors broke the windows of the architect. Official procedure was initiated against more than 20 persons due to the breaking of the windows, which caused losses. The procedure was completed with imposing fines on the affected persons. The shivaree was one of the few folk legal customs carried out due to financial and social reasons. Besides the main underlying motives, the impression of the repugnance was also influenced by political reasons.